Nitrogen use efficiency of open-pollinated maize cultivars and topcrosses under low nitrogen soil - Sunday Ayodele Ige; Bashir Omolaran Bello; Jimoh Mahamood; Michael Afolabi; Charity Aremu; Stephen Abolusoro; Solomon Oyekale; Favour Chijioke (Heliyon)
The study was conducted to evaluate the nitrogen utilization efficiency (NUE) of open-pollinated maize cultivars under low nitrogen soil conditions. It took place at the Lower Niger River Basin Development Authority in Ilorin, Nigeria, during the 2019 and 2020 cropping seasons. The nitrogen treatments (0, 45, and 90 kg N ha⁻1) were assigned as the main plots, while the genotypes were designated as sub-plots in a split-plot design. The NUE of open-pollinated varieties (OPVs) and Topcrosses significantly increased with the application of 45 kg of nitrogen per hectare compared to 0 kg. Similarly, the maize grain yield for both OPVs and Topcrosses ranged from 1.40 to 3.57 t ha⁻1 and from 1.07 to 2.64 t ha⁻1 across the two years with the application of 45 kg of nitrogen per hectare compared to 0 kg. With the exception of days to 50 % silking, all other traits tested exhibited a significant correlation with grain yield. A gene pool for tolerance to low nitrogen may have been present in the cultivars Dmr-Esr Y Cif 2 and Acr 95 Tze Comp 4C3, which combined well with other cultivars to produce high grain yield and NUE. Topcrosses, including Ev Dt-Y 2000 Str C0 × Tze-W Dt Str C4, Dmr-Esr Y Cif 2 × Acr 95 Tze Comp 4C3, Ak 95 Dmr-Esrw × Tzb Rel D4 CO-W, Dmr-Esr Y Cif 2 × Tze-W Dt Str C4, and Br 9922 Dmr Sr × Ev Dt-Y 2000 Str C0, also demonstrated strong potential for maize grain yield and NUE. This suggests that these crosses could serve as promising candidates for developing low nitrogen tolerance in maize for low nitrogen soil environments. A positive relationship between fertilizer levels, NUE, and grain yield indicates that proper nitrogen fertilizer management can enhance both NUE and the grain yield of maize genotypes. Genetic analysis revealed that both phenotypic coefficient of variation (PCV) and environmental variance (δ2p) were higher than genotypic coefficient of variation (GCV) and genetic variance (δ2g), suggesting that environmental influences were more significant than genetic factors for the tested traits. Consequently, improving these traits may be achieved by manipulating environmental conditions.